Menopausal hormone therapy and non-gynecologic cancer (part II) - Oksana V. Iakushevskaia; Svetlana V. Iureneva; Anna E. Protasova; Grigorii N. Khabas; Lev A. Ashrafian (IP Berlin A.V., 2019)
Aim. To carry out a systematic analysis of available researches data on a possibility of using menopausal hormone therapy (MHT) in patients who successfully completed a treatment for malignant neoplasms of different localization. Materials and methods. The review includes data of foreign articles published in PubMed and Medline and domestic articles published in Elibrary.ru over the past 20 years. Results. The data obtained allow us to extend indications range for MHT in patients with history of malignant neoplasms in different organs. This study is one of the few attempts of clinicians to justify the use of MHT as one of the tools for the still imperfect rehabilitation of cancer patients. Conclusion. Patients who successfully completed a treatment for malignant tumors of any localization require special conditions of rehabilitation in order to keep their health and quality of life. A reasonable MHT use in these patients will allow to avoid complications caused by estrogen deficiency followed surgery, radiation with or without systemic (cytostatic) treatment methods.